Frontal Sinus Trauma Presenting with Frontonasal Cutaneous Fistula: A Unique Case Report - Singh, Deepak Kumar; Shankar, Diwakar; Yadav, Kuldeep; Kaif, Mohammad; Singh, Rakesh Kumar (Indian Journal of Neurotrauma, 2023)
Frontal sinus fractures account for 5 to 15% of craniofacial trauma. Road traffic accidents account for most of the cases. Combined injury of the anterior and posterior table with nasofrontal outflow tract contributes to 67% of craniofacial trauma. We here present an interesting case of a 33-year-old male patient with a traumatic left frontal sinus fracture with a unique presentation of a cutaneous–frontonasal fistula. Treatment algorithms for the management of frontal sinus fractures have been proposed in the past but they should be tailored to the need of the individual patient. Obliteration of the frontonasal outflow tract should be advocated in these cases as they minimize complications.
Keywords: frontal sinus fracture; frontonasal outflow tract; craniofacial injury; road traffic accidents; anterior table fracture; frontonasal cutaneous fistula